Physical activity and screen time among youth with autism: A longitudinal analysis from 9 to 18 years. (May 2021) - Dahlgren, J; Healy, S; MacDonald, M; Geldhof, J; Palmiere, K; Haegele, JA
To date, studies using cross-sectional methodologies make up a majority of the literature surrounding children with autism spectrum disorders and participation in physical activity and screen time. Longitudinal studies are needed to examine how physical activity and screen time behaviors co-develop for children with and without an autism spectrum disorder. To address this research gap, this study compared how physical activity and screen time levels changed over time (9 to 18 years of age) between youth with autism spectrum disorder and youth with neurotypical development. Data on the levels of moderate-to-vigorous physical activity, light physical activity, television-, and video game-based screen time, collected as a part of the "Growing up in Ireland" study, were compared between youth with autism spectrum disorder and a propensity-matched sample of youth with neurotypical development ( n = 88 per group; 176 in total). Robust regression analyses indicated that children with autism spectrum disorder became less active over time compared to children with neurotypical development and that video game screen time also differed significantly between the groups when children were 9 years old. These findings elucidate important disparities present between these groups of children during pivotal developmental times. Lay abstract: To date, studies using cross-sectional methodologies make up a majority of the literature surrounding children with autism spectrum disorders and participation in physical activity and screen time. Longitudinal studies are needed to examine how physical activity and screen time behaviors co-develop for children with and without an autism spectrum disorder. To address this research gap, this study compared how physical activity and screen time levels changed over time (from 9 to 18 years of age) between youth with autism spectrum disorder and youth with neurotypical development. Data on the levels of moderate-to-vigorous physical activity, light physical activity, television-, and video game-based screen time, collected as a part of the "Growing up in Ireland" study, were compared between youth with autism spectrum disorder and a propensity-matched sample of youth with neurotypical development ( n = 88 per group; 176 in total). Robust regression analyses indicated that children with autism spectrum disorder became less active over time compared to children with neurotypical development and that video game screen time also differed significantly between the groups when children were 9 years old. These findings elucidate important disparities present between these groups of children during pivotal developmental times.